2021
DOI: 10.2147/prbm.s326994
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Self-Esteem on the Associations Between Infertility-Related Stress and Psychological Distress Among Infertile Chinese Women: A Cross-Sectional Study

Abstract: Background Anxiety and depression are the most common psychological causes of distress in infertile women. Our study aimed to evaluate the prevalence of depression and anxiety and investigate the effects of self-esteem on the association of infertility-related stress with depression and anxiety among infertile women. Methods This study was conducted between December 2017 and May 2018. Questionnaires containing Fertility Problem Inventory (FPI), Rosenberg self-esteem sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 52 publications
4
27
0
Order By: Relevance
“…Self-esteem is an individual’s evaluation of his or her own value. 21 Self-esteem can be used as a mediator variable to alleviate the risk factors caused by infertility. For example, Cui et al found that self-esteem can mediate the effects of infertility, such as stress, depression, and anxiety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-esteem is an individual’s evaluation of his or her own value. 21 Self-esteem can be used as a mediator variable to alleviate the risk factors caused by infertility. For example, Cui et al found that self-esteem can mediate the effects of infertility, such as stress, depression, and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cui et al found that self-esteem can mediate the effects of infertility, such as stress, depression, and anxiety. 21 Self-esteem can also act as a mediator to buffer the impact of the physiological indicators of QoL. Treating migraine and tension-type headache in adolescents can lead to an improved QoL as a result of increased self-esteem.…”
Section: Introductionmentioning
confidence: 99%
“…Infertility is a disease and social problem. According to the reports 9 , about 10-12% of couples are suffering from infertility worldwide. In China, relevant studies have shown [9][10][11] that the prevalence of infertility greatly varies among different regions, with the prevalence among women of childbearing age ranging from 6.7-25%.…”
Section: Discussionmentioning
confidence: 99%
“…According to the reports 9 , about 10-12% of couples are suffering from infertility worldwide. In China, relevant studies have shown [9][10][11] that the prevalence of infertility greatly varies among different regions, with the prevalence among women of childbearing age ranging from 6.7-25%. One of the current methods to solve this problem is to conduct IVF for women of childbearing age with con rmed infertility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation